The Activation and Regulation of β2 Integrins in Phagocytes and Phagocytosis - Sun, Hao; Zhi, Kangkang; Hu, Liang; Fan, Zhichao (Frontiers in Immunology, 2021)
Phagocytes, such as neutrophils, monocytes, macrophages, and dendritic cells, protect the body by removing harmful foreign particles, bacteria, and dead or dying cells. Phagocyte integrins are involved in recognition and adhesion to specific antigens on cells and pathogens during phagocytosis, as well as recruitment. β2 integrins, including αLβ2, αMβ2, αDβ2, and αXβ2, are the major integrins presented on the phagocyte surface. The involvement of β2 integrins in many phagocytic processes is essential to the inflammatory and host defense functions of these phagocytes, making them double-edged swords as candidates for therapeutic intervention. Although β2 integrin blockade has significant benefits in ameliorating autoimmune diseases such as psoriasis, arthritis, and multiple sclerosis, it is also associated with adverse side effects, such as progressive multifocal leukoencephalopathy. Precise regulation of phagocyte activities through β2 integrins should promote their host defense functions with minimal side effects on other cells. Here, we summarize the molecular mechanisms underlying β2 ligand binding, as well as the roles of β2 integrin activation in phagocyte functions.